An exponential Galerkin method for solutions of HIV infection model of CD4+ T-cells. (April 2017) - Yüzbaşı, Şuayip; Karaçayır, Murat
Abstract : Highlights: A new exponential method is proposed for a HIV infection model of CD4 + T-cells. Residual correction method is considered to obtain better approximate solutions. The proposed scheme is compared with some other methods from the literature. Abstract: In this study, we consider a nonlinear first order model about the infection of CD4 + T-cells by HIV. In order to solve it numerically, we present a new method based on exponential polynomials reminiscent of the Galerkin method. Considering the approximate solutions in the form of exponential polynomials, we first substitute these approximate solutions in the original model. Some relations are thus obtained, which we express in terms of matrices. Taking inner product of a set of exponential functions with these matrix expressions then yields a nonlinear system of algebraic equations. The solution of these equations gives the approximate solutions of the model. Additionally, the technique of residual correction, which aims to reduce the error of the approximate solution by estimating this error, is discussed in some detail. The method and the residual correction technique are illustrated with an example. The results are also compared with numerous existing methods from the literature.